Meningkatkan Pengetahuan Mitigasi Bencana Pada Anak Usia Sekolah Melalui Media Game Edukasi “Utas-Gana” di Desa Pindahan Baru - Eva Alviawati; Karunia Puji Hastuti; Parida Angriani; Akhmad Munaya Rahman; Muhhamad Muhaimin (Carmin: Journal of Community Service, 2021)
This counselling and demonstration were conducted to analyze the improvement of disaster mitigation abilities in school-age children through the educational game media "UTAS-GANA" in the New Transfer Village, Rantau Badauh District, Batola Regency. The method used in this activity uses lecture and demonstration methods. This activity was held on Monday, March 7, 2021, in the Village of New Transfer, Rantau Badauh District, Batola Regency. The counselling and demonstrations show an increase in disaster mitigation abilities in school-age children. This activity uses media in the form of an educational game UTAS-GANA (snake and ladder-disaster alert). The learning process about disasters will be well recorded in students' long-term memory.